(untitled) (Balneo and PRM Research Journal, 2024)
The purpose of this study was to determine functional independence measure (FIM) gains based on clinical factors after rehabilitation for cerebrovascular diseases, and to determine how FIM scores and FIM gains can predict rehabilitation outcomes. Of the 181 patients in the study 161 suffered strokes (cerebral infarction 107, cerebral hemorrhage 41, subarachnoid hemorrhage 12, subdural hematoma 1). There were also 12 traumatic brain injuries, and 8 other miscellaneous cases. Dementia, higher brain dysfunction, etiology, sex, age, history of cerebrovascular diseases, location involvement, disability severity, duration of hospitalization and period from onset to rehabilitation were analyzed using FIM. FIM gains decreased in relation to an increase in age. Patients with intermediate disability (FIM 41-80) on admission showed significantly higher FIM-total gain on discharge than others. Factors influencing FIM gain were revealed to be age, duration of hospitalization, FIM gain 4 weeks after admission, etiology, disability severity, dementia and past history of cerebrovascular diseases. Multiple regression analysis determined that significant factors to contribute FIM gain were duration of hospitalization, FIM gain at 4 weeks after admission, age, and disability severity. FIM scores and FIM gains could predict rehabilitation outcomes.